PENGARUH PDRB, SUKU BUNGA, DAN AGEN TERHADAP TABUNGAN LAKU PANDAI DI PROVINSI RIAU PERIODE 2015.Q1 – 2019.Q4 - Zeni Asrul; Rosyetti Rosyetti; Widayatsari Any (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to analyze the influence, pdrb, interest rates, and agents on branchless banking savings in smart behavior in Riau Province in the long and short term 2015.Q1 - 2019.Q4. This research was conducted in Riau Province with the aim of using data from the 2015.Q1 - 2019.Q4 period to produce accurate estimates and conclusions regarding the variables studied and to find out the interpretation of the research object using quarterly data for 5 years. The method used in this research is descriptive and quantitative methods. The analysis model used is multiple linear regression analysis (help of EViews 10 software). The data analysis technique used is the error correction model. As for seeing the effect of independent variables on the dependent variable in the long term and short term where the end result will measure the effect of GDP, interest rates, and agents on branchless banking savings in smart behavior in Riau Province in the long and short term. The results of this study indicate that in the long term, pdrb has a negative and insignificant effect on smart banking branchless savings, interest rates have a positive and insignificant effect on branchless banking savings with smart behavior, and agents have a positive and significant effect on branchless banking savings with smart behavior in the province. Riau. In the short term, pdrb has a positive and insignificant effect on the savings of branchless banking with smart behavior, interest rates have a positive and insignificant effect on savings at branchless banking at smart behavior, and agents have a negative and insignificant effect on savings at branchless banking with smart behavior in Riau Province.Keywords : savings, branchless banking, smart behavior, pdrb, interest rates, agents